1995
DOI: 10.1177/074193259501600408
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Relationship Between Teacher Efficacy and Curriculum-Based Measurement and Student Achievement

Abstract: This study examined the relationship between special education teachers' sense of personal and teaching efficacy and (a) their use of a formative evaluation method (curriculum-based measurement) and (b) the amount of growth they effected among their students. nineteen special education teachers monitored two students with mild disabilities over 16 weeks in math computation using curriculum-based measurement. results indicated that teachers with high personal efficacy and high teaching efficacy increased end-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(121 citation statements)
references
References 31 publications
7
101
1
12
Order By: Relevance
“…Effective special services training workshops and the relative ease with which the Curriculum Based Measurement test procedures can be assimilated by practicing teachers likely had an impact on the high correlation scores. This result supports previous studies of inter-rater reliability ( Shinn, Good, Knutsen, Tilly, Collins, 1992;AUinder, 1995). The results are in agreement with others who have extensively studied reliability and validity o f CBM (Deno, 1985(Deno, , 1992Shinn, 1992;Deno, Mirkin, Marsdon, 1980).…”
Section: Discussionsupporting
confidence: 92%
“…Effective special services training workshops and the relative ease with which the Curriculum Based Measurement test procedures can be assimilated by practicing teachers likely had an impact on the high correlation scores. This result supports previous studies of inter-rater reliability ( Shinn, Good, Knutsen, Tilly, Collins, 1992;AUinder, 1995). The results are in agreement with others who have extensively studied reliability and validity o f CBM (Deno, 1985(Deno, , 1992Shinn, 1992;Deno, Mirkin, Marsdon, 1980).…”
Section: Discussionsupporting
confidence: 92%
“…Newmann, Rutter, and Smith (1989) verified that teaching effectiveness can increase a student's achievement. Allinder (1995) found that the a highly effective teacher can often raise the students' overall learning goal and set up a high expectation to help them achieve better performance. A teacher with high teaching effectiveness will trust he or she can help most of their students to learn, even if they are the most difficult students to teach and who are the least motivated to learn (Guskey, 1988).…”
Section: Teaching Effectivenessmentioning
confidence: 99%
“…On the other hand, teachers' self-efficacy is considered one of the major factors influencing the achievement of educational goals as defined by the institutions and educational centers (Allinder, 1995). Therefore, the notion of teacher self-efficacy has attracted many researchers' attention and has become a seminal area for investigation.…”
Section: Introductionmentioning
confidence: 99%